Special economic zones: An effective instrument for growth in Africa? - Saskia Mösle (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2019)
* Special Economic Zones (SEZs) are an increasingly popular policy instrument aimed at attracting investment and inducing structural change. * Today, there are over 5,000 SEZs worldwide but their economic performance varies widely. * SEZs are particularly widespread in Asia, where they are regarded as a key engine of the export-led growth in recent decades. * In Sub-Saharan Africa, SEZs have been less successful so far, especially due to inadequate planning and implementation of zone programs. * Carefully designed and managed, SEZs have the potential to alleviate shortcomings in the national business climate and to contribute to private sector development.
Keywords: 330